The Overlooked Threat of Hospital Falls During the Discharge Period: A Statewide Retrospective Analysis of Patient Safety Event Reports - Christine E. Sanchez; Rebecca Jones (Patient Safety)
# Background Inpatient falls continue to be a patient safety challenge, with 35,450 falls reported to the Pennsylvania Patient Safety Reporting System (PA-PSRS) in 2024. While previous research has primarily focused on inpatient or post-discharge falls, the transitional period surrounding discharge has been understudied.